Effects of arbuscular mycorrhizal fungi inoculation and phosphorus application on forage crops establishment in a degraded soil - Carneiro, Marco Aurélio Carbone; Siqueira, José Oswaldo; Curi, Nilton; Moreira, Fátima Maria Souza (Pesquisa Agropecuaria Brasileira, 1999)
The effects of increasing doses of phosphorus (0, 50, 100, 200 and 400 mg of P kg-1 of soil) and of inoculation with a mixture of arbuscular mycorrhizal fungi (AMF) upon accumulation of nitrogen and phosphorus and growth of Stylosanthes guianensis, Brachiaria decumbens, Melinis minutiflora and Stylosanthes guianensis - Melinis minutiflora mixed cultivation were evaluated in soil degraded by hydro-electrical dam construction. The experiment was conducted under greenhouse, and three cuts of the aerial part of the plants were performed with an interval of 150 days, and roots were collected only at the last cut. Shoot and root and plant accumulation of N and P in all species responded positively to P. Inoculation with AMF also increased all the above mentioned parameters. The S. guianensis presented low AMF colonization (mean of 4%), but it was very responsive to inoculation with these fungi. The effects of P application upon N accumulation on dry matter yield were also favored by inoculation with AMF. The use of M. minutiflora, that does not depend upon AMF for achieving adequate growth, can be a reasonable strategy for revegetation of degraded soils, without artificial inoculation with AMF.